Determining sequence types of circulating bordetella pertussis strains isolated from South African infants - Smith, Bronwan Margaret Tamzen (My University, 2018)
There is paucity of pertussis disease data from Africa. This study aimed to molecularly characterise B. pertussis strains infecting South African infants to gain knowledge on strains’ antigenic and genetic patterns. Western Blot analysis was done to determine the protein expression of important B. pertussis antigens, namely: pertactin, fimbriae serotypes 2/3 and pertussis toxin, in strains isolated in 2015 from hospitalised infants. The 6 clinical isolates tested had expression for all tested proteins. Additionally, a novel high-throughput single nucleotide polymorphism (SNP) genotyping assay targeting different pertussis toxin promoters (ptxP) was developed and optimised in the Biomark-HD system. We were able to successfully detect 35 recently published SNPs compiled from worldwide whole genome sequencing data. All reactions were effective in amplifying their respective targets in the system. Fifty-two clinical samples positive for B. pertussis by PCR collected during two prospective surveillance studies were retrospectively analysed. The surveillance Babies of Soweto study explored pathogen specific etiology associated with lower respiratory tract hospitalisations in children from the Soweto region while PERCH is a multi-site public health research study on the aetiology and risk factors of pneumonia involving children from South Africa. The expansion of strains containing the more virulent ptxP3 allele was observed from the earlier period of2011-2013 (38.1%) to 2014-2015(65.6%); combined with a decrease in the frequency of the less virulent ptxP1 allele (24.1% in2011-2013 vs.14.7% in 2014-2015). Furthermore, 50% of variability of B. pertussis strains compared to the reference strain was found in unknown genes. In conclusion, we observed no deficiencies in the proteins targeted in most acellular vaccines and that the ptxP3 allele is spreading in this population, as described globally in other studies. A novel SNP typing method was established and this tool will be useful for future studies
A Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Medicine. Johannesburg, 2018
Keywords: Pertussis vacine; Infection in children; Communicable diseases in children